(untitled) (Journal of Enam Medical College, 2024)
Introduction: Like other chronic diseases, CKD patients experience a high symptom burden, reduced quality of life and poor functional status. Identification of these symptoms, measurement of quality of life (QOL) and functional status of these patients by using validated tool and taking necessary steps accordingly is an important aspect of renal supportive care. Objective: Assessment of symptom burden, QOL and functional status in CKD patients (including those on maintenance hemodialysis) and healthy individuals. Materials and Methods: This cross sectional study was conducted in the department of Nephrology of National Institute of Kidney Diseases and Urology, Dhaka from July 2018 to June 2019.The study involved 135 CKD patients (stage 1-5 including those on maintenance hemodialysis) and 30 healthy volunteers. Their demographic profiles were recorded in a data sheet and some routine blood tests were done which included CBC, urinary R/E, serum creatinine, serum urea, serum calcium, serum inorganic phosphate and serum uric acid. Symptom burden was assessed by using Palliative Care Outcome Scale-Symptom Renal (POS-S:Renal) survey, QOL was assessed by using Short Form - 36 survey and functional status was assessed by using Kornofsky Performance Status Scale (KPSS). CKD staging was done by Kidney Disease Improving Global Outcome (KDIGO) (2012) criteria. For the purpose of analysis and discussion, CKD patients were further divided into earlier stage (Stage 1-3) and advanced stage (Stage 4-5). SPSS-22.0A software version was used for data analysis. Results: In this study, it was found that symptom burden was high and quality of life and functional status was reduced in all stages of CKD (mostly in hemodialysis patients) compared to healthy individuals. There was a negative correlation between the glomerular filtration rate (GFR) and symptom burden of the patients. As GFR declined, patient experienced more symptom burden. The most prevalent symptoms reported were weakness, poor mobility, pain and feeling anxious among all stages of CKD. Weakness and poor mobility were also the most severe symptoms in all study population except in healthy individuals where pain was the most prevalent and severe symptom. The mean number of symptoms and total symptom severity score were highest in hemodialysis patients compared with other groups. There was a positive correlation between GFR and quality of life and functional status of patients. All components of physical component summary (PCS) and mental component summary (MCS) score of quality of life and score of functional status decreased as GFR decreased. Regarding biochemical values, there was a positive correlation of serum calcium, serum albumin and hemoglobin level with GFR and a negative correlation of serum phosphate with GFR. Conclusions: High symptom burden, reduced QOL and poor functional status was observed in all stages of CKD and mostly in dialysis patients. Renal supportive care should be applied from the earlier stages for reduction of symptom burden and improvement of QOL and functional status. J Enam Med Col 2022; 12(2): 75−83